Bacterial Community Spacing Is Mainly Shaped by Unique Species in the Subalpine Natural Lakes of China - Liu, Jinxian; Su, Jiahe; Zhang, Meiting; Luo, Zhengming; Li, Xiaoqi; Chai, Baofeng (Frontiers in Microbiology, 2021)
Bacterial communities have been described as early indicators of both regional and global climatic change, and play a critical role in the global biogeochemical cycle. Exploring the mechanisms that determine the diversity patterns of bacterial communities and how they share different habitats along environmental gradients is, therefore, a central theme in microbial ecology research. We characterized the diversity patterns of bacterial communities in Pipahai Lake (PPH), Mayinghai Lake (MYH) and Gonghai Lake (GH), three subalpine natural lakes in Ningwu County, Shanxi, China, and analyzed the distribution of their shared and unique taxa (indicator species). Results showed that the species composition and structure of bacterial communities were significantly different among the three lakes. Both the structure of the entire bacterial community and the unique taxa were significantly influenced by the carbon content (TOC and IC ) and space distance; however, the structure of the shared taxa was affected by conductivity (EC), pH and salinity (SAL). The structure of the entire bacterial community and unique taxa were mainly affected by the same factors, suggesting that unique taxa may be important in maintaining the spatial distribution diversity of bacterial communities in subalpine natural freshwater lakes. Our results provide new insights into the diversity maintenance patterns of the bacterial communities in subalpine lakes, and suggest dispersal limitation on bacterial communities between adjacent lakes, even in a small local area. We revealed the importance of unique taxa in maintaining bacterial community structure, and our results are important in understanding how bacterial communities in subalpine lakes respond to environmental change in local habitats.